"Yay, Another Lady Starting a Log!": Women's Fitness Doping and the Gendered Space of an Online Doping Forum. (December 2021) - Henning, April; Andreasson, Jesper
This study aims to investigate and dissect the meanings attached to women's use of performance and image enhancing drugs (PIEDs), how fitness doping can be understood in terms of gender and spatiality, and what implications this has for women's communicative engagement with one another within an online forum. The study is based on a netnographic and qualitative methodology. Theoretically, it considers a women's online forum for PIEDs and analyzes it as a community of practice (CofP) and a spatiality in which gender, bodies, and side effects are discussed and negotiated. The results show that although the women's forum provides a space for women to share their own unique experiences, there is a limit to the extent to which the discussions mirror the experiences and experimentations of women. Instead, discussions are often dominated by men's voices/experiences. This has two main implications. Firstly, the prevalence of men's voices can block the development of a women's CofP. Symbolically, men engage in a sort of cultural manspreading by encroaching on the women's forum space. Secondly, it has implications for women's PIED use and use practices. Women seeking out advice or the experiences of other women must navigate through and around men's contributions.